Effect of thermal annealing on microstructure evolution and mechanical behavior of an additive manufactured AlSi10Mg part. Issue 12 (29th May 2018) - Yang, Pin; Rodriguez, Mark A.; Deibler, Lisa A.; Jared, Bradley H.; Griego, James; Kilgo, Alice; Allen, Amy; Stefan, Daniel K.
Abstract: Abstract : The powder-bed laser additive manufacturing (AM) process is widely used in the fabrication of three-dimensional metallic parts with intricate structures, where kinetically controlled diffusion and microstructure ripening can be hindered by fast melting and rapid solidification. Therefore, the microstructure and physical properties of parts made by this process will be significantly different from their counterparts produced by conventional methods. This work investigates the microstructure evolution for an AM fabricated AlSi10Mg part from its nonequilibrium state toward equilibrium state. Special attention is placed on silicon dissolution, precipitate formation, collapsing of a divorced eutectic cellular structure, and microstructure ripening in the thermal annealing process. These events alter the size, morphology, length scale, and distribution of the beta silicon phase in the primary aluminum, and changes associated with elastic properties and microhardness are reported. The relationship between residual stress and silicon dissolution due to changes in lattice spacing is also investigated and discussed.